- PERLINDUNGAN INDIKASI GEOGRAFIS MOKE AIMERE : - - Matheus Surya Pribadi Wadapone; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2024)
A cultural heritage product, Moke Aimere has a close connection with the community and geographical conditions in Aimere District. The people of Aimere hope that Moke Aimere can be protected or registered as a Geographical Indication, considering that currently many other parties are using the name "Moke Aimere" as a brand. The formulation of the problem in this research is whether Moke Aimere meets the requirements as a product that can be protected by geographical indications and what obstacles are faced in the process of registering Moke Aimere geographical indications. The research method used is normative using secondary data collection methods (Library Study) in the form of primary, secondary and tertiary data. The results of the research and discussion show that based on Law Number 20 of 2016 concerning Brands and Geographical Indications, the alcohol content in Moke Aimere means that legal protection under the law cannot be obtained because it is contrary to public order. The conclusion obtained based on the research results is that the provisions in Law Number 20 of 2016 concerning Trademarks and Geographical Indications do not provide appropriate legal protection for Moke Aimere. Because Moke Aimere has an alcohol content ranging from 5% -30%, it tends to conflict with public order.